2018
DOI: 10.1111/1756-185x.13404
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐to‐lymphocyte ratio, mean platelet volume and platelet‐to‐lymphocyte ratio in Behçet’s disease and their correlation with disease activity: A meta‐analysis

Abstract: Aim We aimed to evaluate the relationship between mean platelet volume (MPV), neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and Behçet’s disease (BD). Methods We searched Medline, Embase, and Cochrane databases, and performed a meta‐analysis to compare MPV, NLR, and PLR between patients with BD and healthy controls, and to evaluate these parameters in BD according to disease activity and thrombosis. Results In total, 14 studies were included. MPV was not higher in the BD group than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 40 publications
(54 reference statements)
2
47
0
3
Order By: Relevance
“…In the last few years, haematologic parameters such as NLR and PLR have been identified to have predictive value in the diagnosis and prognosis of many diseases. Some studies have reported that these haematologic parameters might have diagnostic value in many chronic diseases such as Behcet syndrome (Lee & Song, ), psoriasis (Paliogiannis et al, ), nonaffective psychosis (Mazza, Lucchi, Rossetti, & Clerici, ) and diabetic nephropathy (Chen et al, ). And several investigations have demonstrated that these haematologic parameters were associated with prognosis of many cancers such as oesophageal cancer (Yodying et al, ), prostate cancer (Guo et al, ) and hepatocellular carcinoma (Zheng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, haematologic parameters such as NLR and PLR have been identified to have predictive value in the diagnosis and prognosis of many diseases. Some studies have reported that these haematologic parameters might have diagnostic value in many chronic diseases such as Behcet syndrome (Lee & Song, ), psoriasis (Paliogiannis et al, ), nonaffective psychosis (Mazza, Lucchi, Rossetti, & Clerici, ) and diabetic nephropathy (Chen et al, ). And several investigations have demonstrated that these haematologic parameters were associated with prognosis of many cancers such as oesophageal cancer (Yodying et al, ), prostate cancer (Guo et al, ) and hepatocellular carcinoma (Zheng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other predictive factors included the presence of CRP and ANC. Derived indexes, such as NLR [36,37] and SII [38] have previously been used as prognostic markers for other inflammatory and autoimmune conditions, as well as in the context of malignant disease, and were also associated with an increased risk of relapse. In our study population, ulceration at presentation was the strongest predictor of recurrence (OR 18.6), and elevated pre‐treatment values of ESR, CPR, ANC, NLR and SII were also associated with a poor prognosis in terms of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The MPV is the mean size of platelets in the serum and reflects the rate and stimulation of platelet production [31]; it is regularly measured using blood count analyzers. Although the role of MPV levels in inflammatory process responses has been investigated in the literature, it remains less studied compared with NLR and PLR [31,32,33]. High-volume platelets have been reported to be critically involved in the infiltration of inflamed tissue [34].…”
Section: Discussionmentioning
confidence: 99%